Strategi Pengembangan Pemasaran Produk Tabungan Tandamata My First pada Bank BJB Cabang Tamansari - Nadia Nur Windari (Bandung Conference Series: Economics Studies, 2024)
Abstract. The number of Tandamata My First savings consumers registered at Bank BJB Tamansari Branch has decreased compared to the number of BTN Junior savings consumers. This happens because of several factors, one of which is fintech. This condition can be a threat to Bank BJB Tamansari Branch which does not yet have superior fintech facilities. This research tries to develop the right marketing development strategy for Bank BJB Tamansari Branch by using SWOT to increase the interest of the number of customers of Tandamata My First savings products at Bank BJB Tamansari Branch. This research uses qualitative research methods with a descriptive approach based on literature studies, interviews, and questionnaires through Google Form. The informant population from this study consisted of 3 customer service, and customers who owned Tandamata My First savings accounts at Bank BJB Tamansari Branch. The sampling techniques used were purposive sampling and snowball sampling methods with a sample of 67 community respondents who used the Tandamata My First savings product whose preferences or opinions were measured using the Likert Scale, and processed into a SWOT analysis. The results of the analysis that have been carried out conclude that Bank BJB Tamansari Branch has an internal strength of 57 and an external factor of 96 which means that it is in the position of quadrant I (positive) where the company has strength and must further develop a marketing strategy that supports aggressive growth policies (growth oriented strategy). The right aggressive strategy for Bank BJB in marketing Tandamata My First savings products is by implementing the concept strategy of segmenting, targeting, and positioning. Abstrak. Jumlah konsumen tabungan Tandamata My First yang terdaftar pada Bank BJB Cabang Tamansari mengalami penurunan dibandingkan dengan jumlah konsumen tabungan BTN Junior. Hal ini terjadi karena beberapa faktor salah satunya fintech. Kondisi ini dapat menjadi ancaman bagi Bank BJB Cabang Tamansari yang belum memiliki fasilitas fintech yang unggul. Penelitian ini mencoba untuk menyusun strategi pengembangan pemasaran yang tepat bagi Bank BJB Cabang Tamansari dengan menggunakan SWOT untuk meningkatkan ketertarikan jumlah nasabah produk tabungan Tandamata My First pada Bank BJB Cabang Tamansari. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif berdasarkan studi kepustakaan, wawancara, dan kuisioner melalui Google Form. Populasi informan dari penelitian ini terdiri dari 3 customer service, dan nasabah pemilik rekening tabungan Tandamata My First pada Bank BJB Cabang Tamansari. Teknik pengambilan sampel yang digunakan adalah metode purposive sampling dan snowball sampling dengan sampel sebanyak 67 responden masyarakat yang menggunakan produk tabungan Tandamata My First yang preferensi atau pendapat nya diukur menggunakan Skala Likert, dan diolah ke dalam analisis SWOT. Hasil dari analisis yang telah dilakukan menyimpulkan bahwa Bank BJB Cabang Tamansari memiliki kekuatan internal sebesar 57 dan faktor eksternal 96 yang artinya berada pada posisi kuadran I (positif) dimana perusahaan memiliki kekuatan serta harus lebih mengembangkan strategi pemasaran yang mendukung kebijakan pertumbuhan secara agresif (growth oriented strategy). Strategi agresif yang tepat bagi Bank BJB dalam memasarkan produk tabungan Tandamata My First yakni dengan menerapkan strategi konsep segmenting, targeting, dan positioning.